Energy flows influence on thermal comfort of outdoor spaces - González, Marina; Machado, María; Barroso, Helen (Rev. Téc. Fac. Ing. Univ. Zulia)
Maracaibo, the second city of Venezuela (1.7 million of inhabitants), has the highest energy consumption index per capita of Latin America, which is a product of the lack of adaptation of the architecture to the environment”™s climate. This situation increases considering that the exterior spaces are designed without any climate control, producing dangerous consequences to the users and to the environment. The main purpose of the research commented in this paper, is to determine, for hot and humid climates, in which proportion the exterior spaces energy flows intervene in the human thermal comfort. The applied procedure considers monitoring and computer simulation of exterior spaces already built. These are analysed comparing the energy gains and loss and the Stress Thermal Index of the human body, under a locally adapted methodology, based on the one used for the exterior areas of Expo”™92 in Sevilla. After the analysis of different variables, design strategies are proposed for the exterior spaces of hot and humid climates.